Price effects of sovereign debt auctions in the Euro-zone: the role of the crisis - Roel Beetsma; Massimo Giuliodori; Frank de Jong; Daniel Widijanto (European Central Bank (ECB), 2013)
Exploring the period since the inception of the euro, we show that secondary-market yields on Italian public debt increase in anticipation of auctions of new issues and decrease after the auction, while no or a smaller such effect is present for German public debt. However, these yield movements on the Italian debt are largely confined to the period of the crisis since mid-2007. We also find that there is some tendency of the yield movements to be larger when the demand for the new issue is smaller relative to its supply. Our results are consistent with a framework in which a small group of primary dealers require compensation for inventory risk and this compensation needs to be higher when market uncertainty is larger. We also find that the secondary-market behaviour of series with a maturity close to the auctioned series, but for which there is no auction, is very similar to the secondary-market behaviour of the auctioned series. These findings support an explanation of yield movements based on the behaviour of primary dealers with limited risk-bearing capacity.
Keywords: G12; G18; 330; Auctions; bid-to-cover ratio; crisis; euro-zone; event; Germany; Italy; primary dealers; public debt; study; yield movements